Peran Pendeta dalam Membangun Kesetiaan Beribadah Remaja Kristen - Martin Putra Hura; Eliezer David Abdiel; Daniel Martin Tamera (Jurnal Pendidikan Agama dan Teologi, 2024)
Many teenagers leave or no longer want to go to church because no one listens or pays attention to teenagers in the church, the role of teenagers in the church is not really appreciated, distrust of the role of teenagers, teenagers want to be guided, not preached to, the church has failed to adapt to today's times and teenagers, there are no facilities to support the development of teenagers in the church, there is no suitable community for teenagers in the church, the church seems to be too overprotective of its people. The purpose of this study, where the pastor must ensure that the needs of adolescents are met in terms of their spirituality and they must be listened to, valued in the church community, so that they feel welcome in the church, then adolescents are given service responsibilities in the church so that they develop their potential. In this study, the researcher used a descriptive qualitative method through literature study, then the researcher interviewed 4 pastors in local churches in the Jakarta area to get answers in this study. the benefits that can be obtained are that Christian teenagers can put their hearts and be loyal to the church where they grow.